Manajemen Zakat dalam Upaya Peningkatan Kesejahteraan Umat - Siti Kalimah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
The obligation to pay zakat in Islam has a basic meaning, zakat is a part of Islam, besides being closely related to the aspect of divinity, it is also closely related to economic and social problems. Zakat is one of the instruments for achieving social welfare. But the fact is, zakat with promising economic potential is not managed optimally, professionally and responsibly. Zakat as an instrument of economy and community welfare, trying to optimize management becomes a necessity because zakat can contribute to improving people's welfare and the love cord between humans (hablunminannas) and connecting the communication of a servant to his Lord (hablunminallah). Community welfare can be supported by the proper use of zakat funds. Moreover, in this day and age the zakat which is the third pillar of Islam, if managed properly it will be able to encourage the country in the economic sector. Zakat is also able to build the economy and prosperity of the people not only from zakat mall, but also from productive zakat. Namely the conversion of zakat funds which were originally from consumptive to productive nature. Which funds collected are not only distributed but also circulated to meet the interests of others on an ongoing basis